A case of central diabetes insipidus after COVID-19 as a probable diagnosis of lymphocytic infundibulo-neurohypophysitis with positive anti-rabphilin-3A antibodies with review of literature - Yuka Natsuki; Yuki Nagata; Toshiki Nagasaki; Mari Morimoto; Norikazu Toi; Masafumi Kurajoh; Tomoaki Morioka; Tetsuo Shoji; Yasuo Imanishi; Naoko Iwata; Haruki Fujisawa; Atsushi Suzuki; et al. (Endocrine Journal)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2, and various complications have been reported. Furthermore, there have been increasing reports of endocrinopathy related to COVID-19 following the pandemic. We report a 49-year-old healthy woman who developed rapid onset of polydipsia and polyuria three weeks after COVID-19. Laboratory tests indicated low urine osmolarity and increased serum osmolarity, and antidiuretic hormone (ADH) was undetectable. Urine osmolality remained low with water deprivation. Similarly, plasma ADH responses to hypertonic-saline infusion were blunted and urine osmolality increased in response to desmopressin. There was no clear evidence of anterior pituitary dysfunction. T1-weighted magnetic resonance imaging (MRI) showed pituitary stalk thickening and absence of posterior pituitary bright signal spots, suggesting the presence of hypophysitis. Based on these results, we made a probable diagnosis of lymphocytic infundibulo-neurohypophysitis (LINH) which have caused central diabetes insipidus. Positive findings for serum anti-rabphilin-3A antibodies, reported as a potential diagnostic marker for LINH, were also noted. Following oral desmopressin administration, polydipsia and polyuria were quickly improved, though treatment with desmopressin was still required over four months. This is the first report of a patient with a probable diagnosis of LINH after COVID-19 who tested positive for anti-rabphilin-3A antibodies. Positive findings for those antibodies suggest that pituitary dysfunction associated with COVID-19 is hypophysitis involving an abnormal immune mechanism. The presence of anti-rabphilin-3A antibodies may be useful as a non-invasive diagnostic marker of LINH and potentially serve as a valuable diagnostic aid in cases of LINH associated with COVID-19.